Neonatal Mortality in Hospitalized Chinese Population: A Meta-Analysis. (13th January 2019) - Zhang, Baoquan; Dai, Yue; Chen, Hanqiang; Yang, Changyi
Abstract : Objective . In this meta-analysis, we aim to investigate the neonatal mortality in hospitalized Chinese population in the recent 20 years in China, which may provide basis for decreasing the neonatal mortality. Methods . The merged mortality was estimated based on the random effect model, and subgroup analysis was performed for the gender, publication year, gestational age, and birth weight. Sensitivity analysis was utilized to evaluate the effects of research type and research quality on the effects. Results . The neonatal mortality in eastern China was lower than that of the central and western China (2.3% versus 2.9; 2.3% versus 26.%). The mortality in neonates with a gestational age of 28-32 weeks (0.6%) was significantly higher than that of <28 weeks (0.1%), 32-37 weeks (0.3%), 37-42 weeks (0.4%), and >42 weeks (0.1%). The mortality in those with a body weight of 1.0-2.5 kg (0.3%) was significantly higher than that of 2.5-4.0 kg (0.2%) and >4.0 kg (0.0%). Sensitivity analysis revealed that the findings of meta-analysis were stable. The major causes for neonatal death included asphyxia, respiratory distress syndrome, and infection. Conclusions . The hospitalized neonatal mortality showed a tendency of decrease, which differed based on gender, region, gestational age, and birth weight.